Seed-borne pathogens and electrical conductivity of soybean seeds - Wain-Tassi, Adriana Luiza [UNESP]; Santos, Juliana Faria dos [UNESP]; Panizzi, Rita de Cássia [UNESP]; Vieira, Roberval Daiton [UNESP] (Universidade de São Paulo (USP), Escola Superior de Agricultura Luiz de Queiroz (ESALQ), 2012)
Adequate procedures to evaluate seed vigor are important. Regarding the electrical conductivity test (EC), the interference in the test results caused by seed-borne pathogens has not been clarified. This research was carried out to study the influence of Phomopsis sojae (Leh.) and Colletotrichum dematium (Pers. ex Fr.) Grove var. truncata (Schw.) Arx. fungi on EC results. Soybean seeds (Glycine max L.) were inoculated with those fungi using potato, agar and dextrose (PDA) medium with manitol (-1.0 MPa) and incubated for 20 h at 25 °C. The colony diameter, index of mycelial growth, seed water content, occurrence of seed-borne pathogens, physiological potential of the seeds, measured by germination and vigor tests (seed germination index, cold test, accelerated aging and electrical conductivity), and seedling field emergence were determined. The contents of K+, Ca2+, and Mg2+ in the seed and in the soaking solution were also determined. A complete 2 × 4 factorial design with two seed sizes (5.5 and 6.5 mm) and four treatments (control, seeds incubated without fungi, seeds incubated with Phomopsis and seeds incubated with Colletotrichum) were used with eight (5.5 mm large seeds) and six (6.5 mm large seeds) replications. All seeds submitted to PDA medium had their germination reduced in comparison to the control seeds. This reduction was also observed when seed vigor and leached ions were considered. The presence of Phomopsis sojae fungus in soybean seed samples submitted to the EC test may be the cause of misleading results.
Keywords: Glycine max; Phomopsis sojae; Colletotrichum dematium var. truncata; Vigor